The shaping ability of WaveOne Gold, TRUShape and XP‐endo Shaper systems in oval‐shaped distal canals of mandibular molars: A microcomputed tomographic analysis. (14th September 2021) - Poly, Ane; Marques, Fernando; Moura Sassone, Luciana; Karabucak, Bekir
Abstract: Aim: To compare the shaping ability of a heat‐treated centric reciprocating file system (WaveOne Gold), a heat‐treated eccentric rotary multifile system (TRUShape 3D Conforming Files), and a heat‐treated expandable one‐file rotary system (XP‐endo Shaper) extending its activation time, in preparing oval‐shaped root canals in extracted mandibular molars by means of microcomputed tomography (micro‐CT) analysis. Methodology: Thirty moderately curved oval‐shaped distal roots of mandibular molars were selected. The normality of canal length, curvature angle, volume, surface area, structure model index, and aspect ratio were confirmed. The samples were randomly divided into three groups ( n = 10). Micro‐CT scans were taken before and after canals were instrumented using WaveOne Gold (size 35, .06 taper), or TRUShape (size 30, .06v taper), both following the manufacturer's instructions, or XP‐endo Shaper following a new protocol with extended activation time. The mechanical preparation time for each sample was recorded. Pre‐ and postoperative images were analysed for the percentage of unprepared canal areas and the percentage of removed dentine. Data were compared between groups using the statistical analyses one‐way ANOVA and Tukey tests ( p < .05). Results: The percentage of unprepared canal areas was significantly higher with WaveOne Gold (% 11.5 ± 4.0) and TRUShape (% 12.4 ± 5.8) compared with XP‐endo Shaper (% 5.2 ± 2.6) ( p < .05). XP‐endo Shaper removed significantly more dentine (3.3 ± 1.5 mm 3 ) than WaveOne Gold (1.8 ± 0.8 mm 3 ) and TRUShape (1.9 ± 0.8 mm 3 ) ( p < .05). No significant differences were seen for mechanical preparation time between WaveOne Gold (79 ± 31 s), TRUShape (104 ± 41 s) and XP‐endo Shaper (71 ± 23 s) ( p > .05). Conclusions: The comparison of three recognized root canal filing systems has shown that with similar preparation times, the XP‐endo Shaper removed more dentine (mm 3 ) leaving less unprepared canal wall area (%) than WaveOne Gold and TRUShape when preparing oval‐shaped root canals of extracted mandibular molars.